Barriers and Initiatives to Access International Market for European Cross-Border Regions - Aristi Karagkouni; Dimitrios Dimitriou (Economies)
This paper explores the role of export-oriented firms in shaping regional economic development, with a focus on their operational footprint, strategic orientation, and interaction with institutional and infrastructural environments. Set within the broader context of regional competitiveness and sustainable growth, the study examines how firms in geographically peripheral and structurally challenged areas position themselves within global markets. Emphasis is placed on understanding the internal and external factors that influence export performance, innovation capacity, and the integration of sustainability principles into business practices. The research adopts a survey-based methodology, collecting data from firms located in a cross-border region to assess their perceptions of trade barriers, infrastructure needs, strategic values, and environmental awareness. The analysis draws on established frameworks in regional development, international business, and sustainability transitions, offering a multidimensional perspective on firm behavior. By linking firm-level insights with regional development policy, the study contributes to ongoing discussions around how enterprises in remote regions can overcome structural constraints and engage more fully with global value chains. It also supports the growing call for place-based, context-sensitive strategies that align economic competitiveness with innovation, digital transformation, and environmental responsibility. This integrated approach offers valuable implications for both policymakers and practitioners concerned with fostering inclusive and resilient regional economies.